Alterations of attention and impulsivity in the rat following a transgenerational decrease in dietary omega-3 fatty acids - Joachim Hauser; Ewelina Stollberg; Andreas Reissmann; Ivo Kaunzinger; Klaus W. Lange (Food Science and Human Wellness)
Polyunsaturated fatty acids (PUFAs), particularly the omega-3 PUFAs, are thought to be involved in neuronal processes, to play a role in neurodevelopmental disorders and to be important for the integrity of central nervous system functioning. The present study investigated the effects of nutritional omega-3 PUFAs on attentional functions and impulsive behavior in Wistar rats. For this purpose, female Wistar rats were fed an omega-3 deficient diet over several generations, and the dams of the seventh generation were randomly assigned to two diet groups and fed an omega-3 deficient or an omega-3 sufficient diet. In addition, a group of previously untreated dams was fed an omega-3 sufficient diet. The male offspring of these three diet groups were tested using an established paradigm for the assessment of attention and impulsive behavior, i.e. a modified version of the five-choice-serial-reaction-time task (5CSRTT). The present data show that the deficiency of omega-3 PUFAs over generations led to substantial changes in attentional processes and impulsive behaviors. The impairments associated with an omega-3 deficiency were partly corrected by treatment with the omega-3 sufficient diet in the last generation of the omega-3 deficient group which showed substantial improvements in attention parameters. While there were no significant effects of dietary modifications on psychomotor activity levels, there was some evidence for changes in impulsive behavior. In conclusion, transgenerational dietary changes in the availability of omega-3 PUFAs led to changes in attentional processes and impulsive behavior in rats, supporting the hypothesis that omega-3 PUFAs play a role in cognitive and behavioral processes. The present findings offer a promising approach in the investigation of the role of omega-3 PUFAs in a variety of cognitive and behavioral domains. Keywords: Omega-3 fatty acid, Polyunsaturated fatty acids, Attention, Impulsivity, Activity, Rat, Neurodevelopmental disorders, Psychiatric disorders